Pengaruh Likuiditas, Profitabilitas, Dan Pertumbuhan Penjualan Terhadap Harga Saham Perusahaan Sub Sektor Makanan Dan Minuman - Aura, Sisi; Efrianti, Desi (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The economy in Indonesia has experienced rapid growth from time to time. This growth is in line with the era of economic globalization faced by the world community. Economic growth will result in changes in the values of people's lives, patterns of life, patterns of thinking and behavior, which have hopes for better public welfare. Today's society has an increasing desire to invest their funds, either in the form of shares, deposits, or in other forms of investment. Basically, investment is the placement of a number of funds at this time to expect rewards that will occur in the future. The research method used in this research is descriptive research with a quantitative approach. The population in this study are food and beverage sub-sector companies listed on the Indonesian stock exchange in 2017-2019. The sampling technique used is purposive sampling. The type of data used in this study is secondary data obtained from the Indonesia Stock Exchange. The data analysis technique used is statistical analysis method using SPSS program. The processing method used is multiple linear regression analysis. There is a negative effect of the current ratio on stock prices in food and beverage sub-sector companies for the 2017-2019 period. This is evidenced by the significance of 0.035 which is smaller than 0.05 or (0.035 < 0.05). There is a positive effect of return on equity on stock prices in food and beverage sub-sector companies for the 2017-2019 period. This is evidenced by the significance of 0.000 which is smaller than 0.05 or (0.000 < 0.05). Sales growth has no effect on stock prices in food and beverage sub- sector companies for the 2017-2019 period. This is evidenced by the significance of 0.947 greater than 0.05 or (0.947 > 0.05). And based on the results of the simultaneous test, it shows that the current ratio, return on equity, and sales growth have an effect on stock prices in food and beverage sub-sector companies for the 2017-2019 period. This is evidenced by the value of the coefficient of determination (R2) obtained by 0.454 and the significance value of the F test of 0.000 which is smaller than 0.05 or (0.000 <0.05).